Factors Influencing Environmental Scanning in the Organizational Context - Zita Correia; T.D. Wilson (Information Research: An International Electronic Journal)
This paper identifies and analyses the factors internal to the organization, which affect the activity of environmental scanning, understood here as the information seeking activity of managers, directed at the company's external environment. These factors include individual factors, such as information consciousness and exposure to information, and organizational factors such as information climate and "outwardness". The main relationships among them are also analysed. These factors were identified in the course of research aiming to provide a comprehensive understanding of the environmental scanning process (Correia & Wilson, 1996). The methodology used - a case-study approach coupled with the grounded theory method of qualitative analysis - was of major importance in obtaining information that is grounded largely on the personal experience of managers.